Dampak Pelaksanaan Tanggung Jawab Sosial terhadap Masyarakat, Lingkungan dan Pemerintah - Matdio Siahaan (Penerbit Goodwood, 2022)
Purpose: To determine the impact of CSR implementation on the Community, the Environment and the Government so that the company can operate in a sustainable manner. The company adheres to the principle of profit orientation but not only that, it includes the company's corporate social responsibility to the community around the company and its environment. Method: This study uses qualitative research methods with the tools of observation, interviews, literature and processing primary and secondary data. This study discusses the role of each stakeholder consisting of the community/environment, companies and the government. Results: From the results of the study, it was found that the implementation of CSR is still not on target so that the community is expected to play an active role in CSR activities to report any deviations in the implementation in the field. Limitations: This study only discusses the impact of CSR implementation from companies engaged in oil palm plantations, it still needs to be investigated from other business fields such as mining,etc. Contribution: Research contributions provide insight and knowledge to the people of Jake Village that companies are obliged to implement CSR and vice versa the company has a responsibility to the community and the environment to maintain harmony for the sustainability of the company's operations.